Evaluating the Drill Method in Maharah Kalam through the Merdeka Curriculum: Rapid Response Drill as an Innovative Speaking Practice Model - Sovia Fahraini; M. Insan Hilmy; M. Baihaqi; Hisbullah Huda (Al-Wazan: Journal of Arabic Education, 2026)
Arabic language learning, in particular maharah kalam, is still dominated by the drill method, which is effective but tends to be mechanistic and does not encourage spontaneity. This study aims to evaluate the implementation and effectiveness of the drill method from the perspective of the Merdeka Curriculum and develop Rapid Response Drill as an alternative speaking practice that is more communicative, contextual, and encourages spontaneous responses. The study used a qualitative evaluative approach with a field research design through learning observations, interviews with teachers and students, and analysis of learning documents in class VIII ICP MTs 2 Nurul Islam. The results showed that drill is effective in strengthening structural accuracy, but creates a dependency on fixed patterns (pattern dependency) so that students' spontaneous response abilities are still limited. Based on these findings, this study developed the concept of Rapid Response Drill, a speaking practice model that combines structural familiarization from the drill method with rapid responses to varied stimuli to train response speed, spontaneity, contextuality, and interactivity. This study contributes theoretically to the development of Arabic language learning methods and practically offers an alternative speaking practice that aligns with the Merdeka Curriculum paradigm.